Introductory clinical pharmacology - Ford, Susan M. (Philadelphia : Wolters Kluwer, 2022)
"Known for its impeccably accurate drug content and proven nursing process approach, Introductory Clinical Pharmacology, 12th Edition, is developed by nurses for nurses, delivering the pharmacologic foundation and clinical judgment skills essential for success on the NCLEX-PN® and in today's nursing practice. Written with client outcomes in mind, this bestselling text not only helps students learn about drugs and their effects on real people, but also teaches students how to effectively relay this information to clients. Straightforward, simplified language makes complex concepts accessible, and a focus on practical application ultimately strengthens adherence to treatment strategies for optimal client outcomes. The extensively updated 12th Edition reflects the latest approaches to basic principles and the nurse's role in medication management, including in-depth coverage of the drug approval process, drug administration, the use of drugs in pain management, and more. Accompanied by powerful online resources - such as videos, NCLEX-PN-style review questions, and drug monographs - it's the perfect resource to hone students' critical thinking and problem-solving skills and prepare them for clinical success"--
Preceded by Roach's introductory clinical pharmacology / Susan M. Ford. Eleventh edition. [2018].
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Pharmacological Phenomena; Drug Therapy; Pharmaceutical Preparations -- administration & dosage; Pharmacology, Clinical -- methods; MEDICAL / Nursing / LPN & LVN; MEDICAL / Pharmacy; Nurses Instruction